Mechanical Test of Plastic Waste Paving Blocks with a Mixture of Candlenut Shells given Compressive Strength Values - Muh. Darmawan Swandi; Mustakim; Muhammad Jabir Muhammadiah (Journal of Civil Engineering and Planning (JCEP), 2025)
Candlenut shells are an organic waste that can be used as a mixed aggregate in making lightweight concrete to reduce environmental pollution. This research aims to analyze the compressive strength performance and the effect of changes in the water absorption capacity of paving blocks made from plastic waste mixed with candlenut shells as a substitute for fine aggregate. Using experimental methods according to the SNI-03-2834-2000 standard, this research was carried out at the Structure and Materials Laboratory of the Muhammadiyah University of Parepare with 12 paving block samples. The results showed that after 3 days, the addition of candlenut shells of 0%, 10%, 15%, and 25% increased the compressive strength of paving blocks of 4,450 MPa, 4,633 MPa, 4,917 MPa, and 5,000 MPa respectively, while the absorption capacity water increases to 1.1%, 1.5%, 1.6%, and 2.0% at the age of treatment The same. The combination of candlenut shell waste with plastic waste has been proven to increase the compressive strength performance of paving blocks, with optimal results obtained by adding 25% candlenut shells. This shows that candlenut shell waste has the potential to be an effective component in paving block mixtures made from plastic waste, while providing dual benefits in reducing waste and improving material quality, thereby contributing to environmental sustainability and advances in concrete technology.